The effect of plyometric training program on agility, jumping, and speed performance in young soccer players - Bahaüddin Türkarslan; Gökhan Deliceoglu (IP Iermakov S.S., 2024)
Background and Study Aim. The aim of this study was to examine the effect of a 6-week plyometric training program on agility, vertical jump, squat jump, and speed performance in soccer players. Material and Methods. A total of 26 male soccer players actively playing for Ankara Batıkent Kartal Sports Club participated in the study as volunteers. The players had an average age of 15.04 ± 0.16 years, an average height of 172.48 ± 5.14 cm, and an average body weight of 62.65 ± 0.38 kg. Data on the players' gender, age, body weight (kg), height (cm), body mass index (BMI), agility, vertical jump (cm), squat jump, and 30 m speed were obtained. Statistical analysis was performed using SPSS 25 software. The normality of the data was examined using the Shapiro-Wilk test. Paired samples t-test was used to determine within-group differences, and independent samples t-test was used to determine differences between groups. A statistical significance level of p < 0.05 was considered for all evaluations. Results. The plyometric training program was effective in improving agility, vertical jump, squat jump, and speed performance in the experimental group. There was a significant difference in agility and 30 m speed values in the pre-test and post-test evaluations of the Control group, but no difference was observed in vertical jump and squat jump values. Additionally, in the pre-test and post-test comparison between the experimental and control groups, a significant difference was observed in agility, vertical jump, and squat jump values. However, no significant difference was found in 30 m speed values. Conclusions. That plyometric training program  is effective in improving agility, vertical jump, squat jump, and 30 m speed values.